The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.1159/000238597
|View full text |Cite
|
Sign up to set email alerts
|

Steady-State Kinetics of Proguanil and Its Active Metabolite, Cycloguanil, in Man

Abstract: The pharmacokinetics of proguanil and its active metabolite, cycloguanil, were determined at steady-state in 6 healthy male volunteers after daily administration of 2 Paludrine® tablets (200 mg proguanil hydrochloride). A maximum plasma proguanil concentration of 130.3 ± 16.0 ng/ml (mean ± SD) was reached at 3.8 ± 1.3 h while a maximum cycloguanil concentration of 52.0 ± 15.2 ng/ml was obtained at 5.3 ± 1.0 h after dosing. The elimination half-lives of proguanil and cycloguanil were 14.5 ± 3.0 h and 11.7 ± 3.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 11 publications
(17 reference statements)
1
4
0
Order By: Relevance
“…Our observation that the mean urinary recovery of PG was about 22% of dose regardless of phenotype (Table 2) is consistent with that of previous studies [23,24] indicating that renal clearance of PG accounted for about 25% of its total clearance. For instance, Wattanagoon et al [24] showed that the mean (± s.d.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our observation that the mean urinary recovery of PG was about 22% of dose regardless of phenotype (Table 2) is consistent with that of previous studies [23,24] indicating that renal clearance of PG accounted for about 25% of its total clearance. For instance, Wattanagoon et al [24] showed that the mean (± s.d.…”
Section: Discussionsupporting
confidence: 92%
“…mean) total clearance of PG was 19.1 ± 2.8 ml minkg-l with a renal clearance of 5.0 ± 1.9 ml min-' kg-' in 10 healthy subjects. In addition, these studies [23,24] suggested that a substantial proportion (up to 60% of dose) of plasma PG clearance remains unaccounted for. In this context, our total 12 h urinary recovery (i.e., PG + CG + CPB) was about 32% in EMs and 23% in PMs.…”
Section: Discussionmentioning
confidence: 99%
“…[14] In vivo, proguanil activation to cycloguanil is a minor metabolic pathway with 11.2 ± 4.2% of the dose excreted in urine as cycloguanil [23]. Renal clearance of proguanil accounts for about 25% of total clearance [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…When comparing the kinetic data of the same individuals following the adminis tration of proguanil alone [16] and pro guanil/dapsone, a significant difference was found in the elimination halflife of PROG which was longer in the combina tion study (18.313.0 h versus 14.513.0 h, p = 0.013). There was, however, no signifi cant difference in the plasma clearance of PROG and in the estimated kinetic values (Cm aX) t/; and AUC) of CYCLO following dosing with proguanil alone and in combi nation with dapsone.…”
Section: Discussionmentioning
confidence: 97%